The Impact of Using Social Users Relationship Management SURM in the Behavioral Component of Consumers’ Attitudes of Insurance Companies Operating in The Syrian Market (Journal of Hama University, 2022)
The research aimed to study the impact of Using Social Users Relationship Management SURM in the Behavioral Component of Consumers’ Attitudes of Insurance Companies Operating in The Syrian Market. The descriptive approach was adopted, and an electronic questionnaire was designed, and published in the virtual Facebook community; Where 288 responses valid for analysis were obtained from a sample of consumers (actual and potential) for the insurance market in Syria. The most important findings of the research were that there was a significant impact of each of the dimensions of social users relationship management (involving users in interactive conversations, building trust, improving user experience, engaging the user in service development) in the behavioral component of Consumers’ Attitudes of the studied corporate. However, with the emergence of a weakness in the optimal investment of the potential of social media and benefiting from them with regard to social users relationship management systems to reach the appropriate impact on the behavioral intentions of customers..